2023
DOI: 10.1007/s40264-023-01274-8
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Deaths Involving Medicines: A Systematic Case Series of Coroners’ Reports 2013–22

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…After screening and removing duplicates, 17 studies 13,1530 that examined PFDs in England and Wales were included (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening and removing duplicates, 17 studies 13,1530 that examined PFDs in England and Wales were included (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In this narrative review, we identified 17 studies 13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] that analysed PFDs in England and Wales. PFDs documenting deaths related to medicines and drugs were explored most (47%; n = 8), followed by deaths involving healthcare (24%; n = 4) and chemical products (12%; n = 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations